Developing an approach for evaluating the cardiotoxic potential of botanicals - Krzykwa, Julie; Chaudhari, Hemantkumar S.; Monteiro Da Rocha, Andre; Gossmann, Matthias; Hoffmann, Peter; Khokhar, Yaser; Meyer, Nathan; Park, Jin-Young K.; Sprando, Robert; Vaidyanathan, Ravi; Westerink, Remco H. S.; Wu, Joseph C.; et al. (Frontiers in Toxicology, 2025)
Botanicals (e.g., extracts derived from plants, algae, or fungi) are increasingly utilized by consumers with the hope of enhancing their health, managing symptoms, or preventing ailments; however, these products have often had limited pre-market toxicity testing. Traditional toxicity testing (e.g., rodent testing) is complicated by the nature of botanicals as complex mixtures and the potential for lot-to-lot variability in chemical constituents. Cardiotoxicity is a key area of concern, as adverse effects on the cardiovascular system can have severe consequences, and although not commonly reported, there have been reports of adverse cardiac events. New approach methodologies (NAMs) offer human-relevant, efficient, innovative, and cost-effective solutions for evaluating the cardiotoxicity of botanicals. The Botanical Safety Consortium (BSC) was established to focus on identifying suitable NAMs to screen for potential toxicities associated with these widely used products. This manuscript outlines the BSC Cardiotoxicity Working Group’s approach for evaluating NAMs for assessing the potential cardiotoxicity of botanicals. These NAMs leverage in vitro models, such as human-induced pluripotent stem cell-derived cardiomyocytes, and techniques like microelectrode arrays, voltage and calcium optical mapping, contractile force measurement, and mitochondrial function assays to evaluate botanical-induced effects on the cardiovascular system. Using well-characterized botanical extracts as case studies, the BSC aims to refine a toolkit for high-throughput and human-relevant cardiotoxicity screening. This foundational work supports the broader goal of improving botanical safety assessment practices and advancing the application of NAMs in regulatory toxicology.